GATA3 induces the pathogenicity of Th17 cells via regulating GM-CSF expression - Butcher, Matthew J.; Gurram, Rama Krishna; Zhu, Xiaoliang; Chen, Xi; Hu, Gangqing; Lazarevic, Vanja; Zhao, Keji; Zhu, Jinfang (Frontiers in Immunology, 2023)
T-bet-expressing Th17 (T-bet + RORgt + ) cells are associated with the induction of pathology during experimental autoimmune encephalomyelitis (EAE) and the encephalitic nature of these Th17 cells can be explained by their ability to produce GM-CSF. However, the upstream regulatory mechanisms that control Csf2 (gene encoding GM-CSF) expression are still unclear.In this study, we found that Th17 cells dynamically expressed GATA3, the master transcription factor for Th2 cell differentiation, during their differentiation both in vitro and in vivo. Early deletion of Gata3 in three complimentary conditional knockout models by Cre-ERT2, hCd2 Cre and Tbx21 Cre , respectively, limited the pathogenicity of Th17 cells during EAE, which was correlated with a defect in generating pathogenic T-bet-expressing Th17 cells. These results indicate that early GATA3-dependent gene regulation is critically required to generate a de novo encephalitogenic Th17 response. Furthermore, a late deletion of Gata3 via Cre-ERT2 in the adoptive transfer EAE model resulted in a cell intrinsic failure to induce EAE symptoms which was correlated with a substantial reduction in GM-CSF production without affecting the generation and/or maintenance of T-bet-expressing Th17 cells. RNA-Seq analysis of Gata3sufficient and Gata3-deficient CNS-infiltrating CD4 + effector T cells from mixed congenic cotransfer recipient mice revealed an important, cell-intrinsic, function of GATA3 in regulating the expression of Egr2, Bhlhe40, and Csf2. Thus, our data highlights a novel role for GATA3 in promoting and maintaining the pathogenicity of T-bet-expressing Th17 cells in EAE, via putative regulation of Egr2, Bhlhe40, and GM-CSF expression.